PENGARUH FAKTOR – FAKTOR PEMBENTUK PERILAKU KONSUMEN DALAM PEMBELIAN FOOTWEAR MEREK “X” - Evi Thelia Sari; Sylvia Wirawan (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
This research is to test that culture, social, personal and psychological factors will affect to customer’s buying behaviour towards “X” Footwear  products. Culture factor consists of color, flat heels, community acceptance; Social factor in this research consists of family, friend and community; personal factor includes model, lifestyle, quality, price, need and interest; psychology is supported by recommendation, good using experience, product availability, and eagerness to try new brand. The respondents were taken in Central Java. Using multiple regression linear analysis, this research shows the result that physicological factor has the biggest and most significant influence towards the consumer’s behaviour at 0.000for t-test, followed by social (sig t = 0.033), culture (sig t=0.038) and personal factor (sig t=0.046).